Tingkat Cemaran Mikrobia pada Tanaman Biofarmaka Curcuma domestica setelah Proses Pengeringan - Kusumaningrum, Hermin Pancasakti (Prosiding KPSDA, 2015)
Solar food processing is an emerging technology that provides good quality foods and economist. Traditional medicinal plants product such as turmeric (C. domestica) drying product from local industries on Gunungpati Semarang have not meet its standards quality yet, in terms of microbial contaminants. The purpose of this research is to test the drying product resulted from heating process of simplicia by sunlight and oven. Observations of focusing on microbial contaminant from treatment after 3 month incubation. The research method conducted by drying simplicia of C. domestica at variant a temperature of 300C, 400C, 500C and 600C for 1, 3, 6, 9, 12, 24, and 48 hours. The results showed that drying at a temperature of 500C and 600C for 24 hours and 48 hours showed the lowest contamination and still in accordance with ISO standard for simplicia which is number of mold and yeast <1´104 cfu, while the total plate count were <1´107cfu.